주관절 일차성 골관절염 환자에서 관절경적 전방 구획 변연 절제술 및 후방 구획 최소 절개 절제술과 관절경적 전 · 후방 구획 변연 절제술의 임상적 결과의 비교 - 천상진(Sang Jin Cheon); 문규필(Kyu Pill Moon); 서한얼(Han Eol Seo); 강준호(Jun Ho Kang) (The journal of the Korean Orthopaedic Association, 2022)
목적: 중등도 이하의 주관절 일차성 골관절염 환자의 수술적 치료 방법 중 관절경적 전방 구획 변연 절제술 및 후방 구획 최소 절개절제술의 유용성에 대해 알아보고자, 관절경적 전·후방 변연 절제술과 임상적 결과를 비교하였다. 대상 및 방법: 2010년 1월부터 2016년 12월까지 본원에서 주관절 골관절염으로 진단되어 관절경적 전방 구획 변연 절제술과 후방 구획 최소 절개 절제술 또는 관절경적 전·후방 변연 절제술을 시행 받은 46명 중 27명을 최종 대상으로 선정하여 관절경적 전방 구획 변연 절제술과 후방 구획 최소 절개 절제술을 받은 16명의 환자를 1군, 관절경적 전·후방 변연 절제술을 시행한 11명을 2군으로 구분하여 의무기록 조사를 통해 후향적 연구를 시행하였다. 수술 전과 수술 후 최종 추시에서의 주관절 굴곡 및 신전관절 운동 범위(range of motion, ROM), 시각통증척도(visual analogue scale, VAS), 메이요 팔꿈치 성능 점수(Mayo Elbow Performance Score, MEPS)를 이용하여 임상적 결과를 분석하였다. 결과: 평균 추시 기간은 21개월(15–32개월)이었으며, 임상적 지표인 ROM, VAS, MEPS는 1, 2군 모두 수술 후 유의하게 향상되었고(p＜0.05), 두 군의 비교에서는 굴곡(p-value=0.001) 및 전체 ROM (p-value=0.011)가 1군에서 좀 더 유의한 증가폭을 보였으며 신전, VAS, MEPS는 유의한 차이가 보이지 않았다. 결론: 주관절 일차성 골관절염 환자에서 시행한 관절경적 전방 구획 변연 절제술 및 후방 구획 최소 절개 절제술은 수술 후 임상적결과가 우수하였으며, 특히 굴곡 및 전체 ROM 향상에 도움이 되는 유용한 술식으로 생각된다 Purpose: This study analyzed the effectiveness of arthroscopic anterior compartment debridement with posterior mini-open debridement in patients with mild or moderate primary elbow osteoarthritis (OA). The clinical results of arthroscopic anterior compartment debridement with posterior mini-open debridement were compared with that of arthroscopic both compartments debridement. Materials and Methods: Between January 2010 and December 2016, 46 patients diagnosed with elbow OA underwent arthroscopic anterior compartment debridement with posterior mini-open debridement or arthroscopic anterior and posterior compartments debridement arthroscopic surgery. Of these, 27 patients were finally included in this study. The data were collected retrospectively from the medical records. The subjects were divided into two groups according to the surgical procedure: group 1 (n=16) received arthroscopic anterior compartment debridement with posterior mini-open debridement surgery, and group 2 (n=11) received arthroscopic anterior and posterior compartments debridement surgery. The elbow flexion-extension range of motion (ROM), visual analog scale (VAS), Mayo Elbow Performance Score (MEPS) were analyzed for the clinical outcome before surgery and the last follow-up visit after surgery. Results: The average follow-up period was 21 months (15–32 months). All clinical outcomes (ROM, VAS, and MEPS) were improved after surgery compared to those before surgery (p<0.05) in both groups. Group 1 showed further improvement in flexion (p=0.001) and total ROM (p=0.011) than group 2. On the other hand, there was no significant difference in extension, VAS, and MEPS between the two groups. Conclusion: In patients with primary elbow OA, arthroscopic anterior compartment debridement with posterior compartment mini-open technique produced an excellent clinical outcome after surgery and was particularly helpful in increasing flexion and the total ROM. KCI Citation Count: 0